KONSEP KELUARGA SAKINAH DI ERA DIGITAL (STUDI ANALISIS PEMIKIRAN SYEKH MUTAWALLI SYA’RAWI DALAM TAFSIR SYA'RAWI) - Matondang, Miftahul Jannah; Rambe, Khairul Mufti (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study examines the concept of the family within Sheikh Mutawalli Sha'rawi's Qur'anic exegesis (tafsir) and its relevance for Muslim families in the digital age. Employing a qualitative library research method, the study analyzes primary sources, namely the Qur'an and Sha'rawi's exegetical works, along with related secondary sources. The findings indicate that Sha'rawi interprets QS. Ar-Rum (30:21) as articulating the spiritual foundation of the family, emphasizing sakinah (tranquility), mawaddah (affection), and rahmah (mercy) as the core pillars of domestic harmony. The study connects this classical exegetical thought with contemporary challenges, such as communication disruption, social media dependency, and the erosion of parental oversight in technology use. The research affirms that Sha'rawi's framework remains relevant for building resilient Muslim families that are adaptive, harmonious, and grounded in Islamic spirituality. It is concluded that the internalization of Qur'anic values and the strengthening of faith-based digital literacy are necessary to enable Muslim families to respond positively to social changes in the modern era.